Capitalist crisis in the "age of global value chains". (September 2021) - Bair, Jennifer; Mahutga, Mathew; Werner, Marion; Campling, Liam
In this article, we analyze the strategies, surprises, and sidesteps in the World Bank's 2020 World Development Report, Trading for Development in the Age of Global Value Chains . Strategically, the Report promotes an expansion of neoliberal globalization couched in the language of global value chains. Curiously detached from the broader academic literature on global value chains in international trade, it promotes a sequentialist vision of global value chain upgrading that evokes the stagism of classic modernization theory. The authors sidestep important issues, such as China's pivotal role in the landscape of global trade, and are largely silent on others, including climate change. Significantly and somewhat surprisingly, given the general endorsement of global value chain integration, the Report acknowledges negative distributional trends associated with the rise of global value chains, including the excessive benefits reaped by "superstar firms" and the now well-documented decline in labor's income share. These observations are not reflected in the document's policy section, however, where the World Development Report largely recapitulates familiar prescriptions, with the threat of nationalist populism and rising protectionism providing a new bottle for this old wine. Drawing on a range of literature including United Nations Conference on Trade and Development's 2018 Trade and Development Report, we highlight not only the limits of the Bank's adherence to an increasingly embattled orthodoxy, but also the necessary starting points for a more useful discussion of the merits, limits, and future of global value chains.